2017
DOI: 10.7202/1042238ar
|View full text |Cite
|
Sign up to set email alerts
|

Les élections partielles au Québec

Abstract: Les élections partielles ont-elles les mêmes caractéristiques et suivent-elles les mêmes tendances que les élections générales ? Nous proposons une analyse du taux de participation et de la performance des petits partis lors des élections partielles québécoises depuis 1970. Nous examinons également la performance des députés élus lors de partielles aux élections générales subséquentes. Finalement, nous vérifions si les élections complémentaires constituent, comme plusieurs le pensent, des référendums sur le go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…What can be explored is what conditions are associated with aggregate-level turnout in special elections moving up or down. Two studies in Canada (Blais-Lacombe and Bodet, 2017;Loewen and Bastien, 2010) found turnout in special elections mirrored patterns associated with turnout in general elections, with the characteristics of the special election in question having less impact. This article follows suit by testing if turnout in Irish by-elections mirrors general patterns of turnout in general elections or if the contextual circumstances of the by-election itself have a stronger association.…”
Section: Turnoutmentioning
confidence: 99%
See 3 more Smart Citations
“…What can be explored is what conditions are associated with aggregate-level turnout in special elections moving up or down. Two studies in Canada (Blais-Lacombe and Bodet, 2017;Loewen and Bastien, 2010) found turnout in special elections mirrored patterns associated with turnout in general elections, with the characteristics of the special election in question having less impact. This article follows suit by testing if turnout in Irish by-elections mirrors general patterns of turnout in general elections or if the contextual circumstances of the by-election itself have a stronger association.…”
Section: Turnoutmentioning
confidence: 99%
“…In essence, the referendum model challenges the premise by-elections are merely local contests and assumes they can be viewed through a national prism, with voters using them to send a message to the government. The referendum model has received strong support in accounting for special election outcomes in Britain (Mughan, 1986(Mughan, , 1988Norris, 1990), Canada (Blais-Lacombe and Bodet, 2017;Loewen and Bastien, 2010), the United States (Gibbs et al, 2016;Sigelman, 1981) and in cross-national studies (Anderson and Ward, 1996;Feigart and Norris, 1990).…”
Section: Government Performancementioning
confidence: 99%
See 2 more Smart Citations
“…By-elections, or the process of filling a legislative seat between general elections, are a regular aspect of many parliamentary systems throughout the world. Despite this regularity, by-elections are significantly understudied compared to other electoral processes (Mughan 1986;Feigert and Norris 1990;Loewen and Bastien 2010;Blais-Lacombe and Bodet 2017). By-elections in Canada are particularly an understudied phenomenon (Kay 1981;Massicotte 1981;Feigert and Norris 1990;Loewen and Bastien 2010;Blais-Lacombe and Bodet 2017).…”
Section: Introductionmentioning
confidence: 99%